Inflammation and Clinical Decline After Adjuvant Chemotherapy in Older Adults With Breast Cancer: Results From the Hurria Older Patients Prospective Study. Issue 2 (20th September 2022) - Ji, Jingran; Sun, Can-Lan; Cohen, Harvey J.; Synold, Timothy; Muss, Hyman; Sedrak, Mina S.
Abstract : PURPOSE: Older breast cancer survivors are at increased risk of clinical decline after adjuvant chemotherapy. This study aimed to evaluate whether inflammatory markers assessed before adjuvant chemotherapy are associated with chemotherapy-induced clinical decline in a population of fit older adults with breast cancer. METHODS: In a prospective study of women age ≥ 65 years with stage I-III breast cancer treated with chemotherapy, we measured interleukin-6 (IL-6) and C-reactive protein (CRP) prechemotherapy (T1). We assessed frailty status, using a Deficit Accumulation Index (DAI; categorized as robust, prefrail, and frail), at T1 and postchemotherapy (T2). The population of interest was robust women at T1. The primary outcome was chemotherapy-induced decline in frailty status, defined as decline in DAI from robust (T1) to prefrail or frail (T2). Multivariable logistic regression was used to examine the association between inflammatory markers and the primary outcome, adjusted for sociodemographic and clinical characteristics. RESULTS: Of the 295 robust women at T1, 76 (26%) experienced chemotherapy-induced decline in frailty status, among whom 66% had high IL-6, 63% had high CRP, and 46% had high IL-6 and CRP at T1. After adjusting for sociodemographic and clinical characteristics, women with high IL-6 and CRP had a > three-fold (odds ratio, 3.52; 95% CI, 1.55 to 8.01; P = .003) odds of chemotherapy-induced decline in frailty status compared with women with low IL-6 and CRP. CONCLUSION: In this cohort of older women with early breast cancer who were clinically fit before chemotherapy initiation, high IL-6 and CRP prechemotherapy were associated with chemotherapy-induced decline in frailty status independent of sociodemographic and clinical risk factors. Further research is needed to examine whether inflammatory markers can inform more personalized approaches to treating older breast cancer survivors.